Practices of Reusing Cooking Oil and Peroxide Values Among Pecel Lele Vendors Around the Universitas Sriwijaya Campus: IN PRESS - Riska Seliana; Dini Arista Putri; Frisca Rahmadina; Imelda Gernauli Purba (Jurnal Ilmu Kesehatan Masyarakat, 2026)
Repeated use of cooking oil by pecel lele vendors may accelerate oil degradation and increase peroxide formation, posing potential health risks. Study aimed to explore vendors’ knowledge and practices regarding reused cooking oil and to describe the peroxide values of oil samples collected around the Universitas Sriwijaya Campus. A qualitative descriptive design with supplementary laboratory analysis was used. Twenty informants were selected purposively, comprising seven vendors, twelve consumers, and one chemistry expert. Data were collected through in-depth interviews, observation, documentation, and laboratory testing. Six reused oil samples were analyzed for peroxide values using the iodometric titration method at BSPJI Palembang. Data validity was ensured through source and method triangulation. Most vendors and consumers understood the general meaning and visible characteristics of reused cooking oil, but none knew the definition, health implications, or permitted limit of peroxide values. Vendors commonly reused oil more than four times, mixed old oil with new oil, used the same oil and wok for different foods, and stored used oil in open containers. Deep-fat frying with high heat and relatively long heating durations was also observed. All six oil samples exceeded the maximum peroxide value of 10 mEq O₂/kg stipulated in SNI 7709:2019, ranging from 14.96 to 2,313.07 mEq O₂/kg. These findings indicate that unsafe oil-reuse and storage practices were common among the participating food vendors and occurred alongside peroxide values above the permitted limit. Practical education, regular oil replacement, filtration, safer storage, and better control of frying duration are recommended to improve food safety